Cultivating Global Citizens: Population in the rise of China - Greenhalgh, Susan (London Harvard University Press, 2010)
Current accounts of China's global rise emphasize economics and politics, largely neglecting the cultivation of China's people. Susan Greenhalgh , one of the foremost authorities on China's one-child policy, places the governance of population squarely at the heart of China's ascent.
Keywords: Birth control -- China; Family size -- Government policy -- China; China -- Politics and government